Analisis Kualitas Air Tanah pada Daerah Sekitar Lokasi Pertambangan di Kabupaten Kolaka - Ali Okto; Al Rubaiyn; Jahidin; La Ode Sahiddin; La ode Andimbara; Suryawan Asfar (Jurnal Rekayasa Geofisika Indonesia, 2023)
This research was conducted around mining sites is Pomalaa district, Kolaka. Nickel mining activities have an impact on water pollution which can reduce water quality in both rivers and groundwater. The decrease in water quality around the mining area can be caused by the flow of runoff from rainwater which carries soil particles to water bodies which makes the water cloudy and may contain heavy metals. This study aims to determine the quality of the soil around the mining area of ​​Pomalaa District. Sampling of surface water and subsurface water was carried out using the purposive sampling method. The Pollution Index method is used to analyze the level of water pollution. The results of the analysis show that mining activities in the study area do not have a significant impact on decreasing air quality even though some hazardous metal elements are found such as Arsenic (Ar), Khomium VI (Cr+6), Iron , Cadmium, Copper (Cu) and Lead (Pb). The dominant influence is the high content of BOD and DO in the waters which makes several locations of minor occurrences according to the calculation of indexing calculations. Geological factors that play a role in decreasing air quality are morphological, lithological and structura